Propensity score matched mortality comparisons of peritoneal and in-centre haemodialysis: systematic review and meta-analysis. Issue 12 (28th January 2020) - Elsayed, Mohamed E; Morris, Adam D; Li, Xia; Browne, Leonard D; Stack, Austin G
Abstract: Background: Accurate comparisons of haemodialysis (HD) and peritoneal dialysis (PD) survival based on observational studies are difficult due to substantial residual confounding that arises from imbalances between treatments. Propensity score matching (PSM) comparisons confer additional advantages over conventional methods of adjustment by further reducing selection bias between treatments. We conducted a systematic review of studies that compared mortality between in-centre HD with PD using a PSM-based approach. Methods: A sensitive search strategy identified all citations in the PubMed, Cochrane and EMBASE databases from inception through November 2018. Pooled PD versus HD mortality hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated through random-effects meta-analysis. A subsequent meta-regression explored factors to account for between-study variation. Results: The systematic review yielded 214 citations with 17 cohort studies and 113 578 PSM incident dialysis patients. Cohort periods spanned the period 1993–2014. The pooled HR for PD versus HD was 1.06 (95% CI 0.99–1.14). There was considerable variation by country, however, mortality risks for PD versus HD remained virtually unchanged when stratified by geographical region with HRs of 1.04 (95% CI 0.94–1.15), 1.14 (95% CI 0.99–1.32) and 0.98 (0.87–1.10) for European, Asian and American cohorts, respectively. Subgroup meta-analyses revealed similar risks for patients with diabetes [HR 1.09 (95% CI 0.98–1.21)] and without diabetes [HR 0.99 (95% CI 0.90–1.09)]. Heterogeneity was substantial ( I 2 = 87%) and was largely accounted for by differences in cohort period, study type and country of origin. Together these factors explained a substantial degree of between-studies variance ( R 2 = 90.6%). Conclusions: This meta-analysis suggests that PD and in-centre HD carry equivalent survival benefits. Reported differences in survival between treatments largely reflect a combination of factors that are unrelated to clinical efficacy. GRAPHICAL ABSTRACT: